Comportamento do maracuajazeiro amarelo, variedade Afruvec, ante uma população de Fusarium solani, agente causal da podridão do colo - Bueno, Cesar Junior; Fisher, Ivan H.; Parisi, Marise C. M.; Furtado, Edson Luiz [UNESP] (My University, 2010)
The objective of the present work was to verify the behavior of yellow passion fruit, Afruvec variety, in relation to a population of Fusarium solani, obtained from this crop. The experimental delineation was random blocks, containing 10 treatments [9 isolates and 1 control treatment], with 4 repetitions, each plot being represented by a vase containing a plant. A disk of culture medium colonized by each isolate of the fungus was inoculated in the wounded collar region of the plants of the Afruvec variety two months after sowing. The appraised parameters were: the pathogenicity, the incidence (number of dead plants) and the severity of the disease (length of the lesion in the collar region), until 60 days after inoculation. The Afruvec variety was susceptible to the fungus and also presented variability as to the severity of the disease and incidence in relation to the different isolates. The population of the fungus showed variability in regard to aggressiveness. In light of the evidence of genetic diversity in the F. solani population, it is also suggested, in the tests of selection of materials to the pathogen, that these materials should be evaluated in different places with a history of the disease or inoculation with a pool of isolates of the fungus, in order to know the wide resistance of the genotype to the pathogen.

O objetivo do presente trabalho foi verificar o comportamento do maracujazeiro amarelo, variedade Afruvec, ante uma população de Fusarium solani, obtida desse mesmo hospedeiro. O delineamento adotado foi o de blocos ao acaso, contendo dez tratamentos (nove isolados e tratamento testemunha), com quatro repetições, sendo cada parcela representada por um vaso contendo uma planta. Um disco do meio de cultura, colonizado com cada isolado do fungo, foi inoculado no colo ferido das plantas da variedade Afruvec, dois meses após a semeadura. Avaliou-se a patogenicidade, a incidência (número de plantas mortas) e a severidade da doença (comprimento da lesão no colo), até os sessenta dias após a inoculação. A variedade Afruvec foi suscetível ao fungo e apresentou variabilidade quanto à incidência e severidade da doença diante dos diferentes isolados. A população do fungo apresentou variabilidade em relação à agressividade. Com a evidência de diversidade genética na população do fungo, recomenda-se, também, nos testes de seleção de materiais ao patógeno, a avaliação desses materiais em diferentes localidades com histórico da doença ou inoculação com uma mistura de isolados do fungo, a fim de se conhecer a resistência ampla do genótipo ao patógeno.
Behaviour of yellow passion fruit, afruvec variety, in relation to a population of fusarium solani, causal agent of collar rot
Keywords: Maracujá; Melhoramento genético; Resistência genética; Fusarium solani; Variabilidade genética